LANGUAGE AND SPEECH IN MENTAL ACTIVITY - Ахмедова Муяссар Хадиматовна; Джумабаева Манзура Багибековна (Ecominds Press, 2025)
Much attention is currently paid to the scientific study of the psycholinguistic features of the national language. This article examines the mental properties of the personal lexicon. in the formation of speech skills, the role of the psyche in the acquisition and use of language by a person is important. Differences in thinking, distinctive features are manifested in the speech activity of an individual. The emergence of speech (in connection with the child's organism - its formation) significantly restructures the entire mental sphere of a person. Such processes as perception, memory, thinking, imagination, voluntary attention are formed and mediated in a person only with the participation of speech. The article scientifically describes the mental properties of the human lexicon.
Keywords: Language, psycholinguistics, speech, vocabulary, perception, memory, communication, speech activity, lexicon, attention, intuition, consciousness, mental activity.